Kerukunan Ummat Beragama Islam dan Kristen di Polman - Hasbi (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
The era of globalization makes the relationship between humans and between religions in Polman closer to Islam and Christianity. Sophisticated technology makes communication between religious communities more intimate. However, in this highly developed era, the behavior of a handful or a group of uncivilized humans is still very much against religious teachings, and can even threaten religious harmony in Polman. The purpose of this research is, first, how the harmony of the Muslim and Christian communities is, Second, the forms of Islamic and Christian community harmony activities, Third, what are the driving and inhibiting factors for religious harmony in Polman. The method uses qualitative research with data collection techniques of observation, interviews, and analysis. The results of religious harmony in Polman must be built and we believe that inter-religious harmony is the main element of national harmony. For the Muslim and Christian communities in Polman, the celebration of the Indonesian Independence Day is a medium to establish good communication between them. Muslims and Christians carry out joint activities to celebrate the Indonesian Independence Day in various activities, religious harmony is a state of inter-religious relations based on tolerance, mutual understanding and mutual respect. Conclusion For years, the Polman community has made efforts so that this diverse community lives in harmony. Inter-religious harmony between Islam and Christianity is one of the main pillars in maintaining the unity and harmony of Islamic and Christian communities in Polman. Harmony is often interpreted as living and living conditions that reflect an atmosphere of peace, order, peace, prosperity, respect, respect, respect, tolerance, mutual cooperation in accordance with the teachings of each religion. Keywords: Harmony, Islam, Christianity.